Combined experimental and numerical investigation of multiphase flow during water entry of spheres with different densities. (April 2023) - Li, Daqin; Zhang, Mindi; Huang, Biao; Li, Lijian; Hu, Wenbin
Highlights: A combined of experimental and numerical investigation is used in the research. The numerical method is based on the N-S equations with wettability. The splash and cavity of water-entry spheres with varied densities are studied. The motion and hydrodynamic characteristics of the sphere are analyzed. The total hydrodynamic force and drag force are compared and discussed. Abstract: The objective of this work is to investigate the cavity dynamics during water entry of spheres with varied structural density by a combined experimental and numerical method. Similar to the observations of Aristoff et al. (2009), the cavity types are further classified considering the relationship between the splash and cavity, then a map of cavity types in a Froude number and density ratio ( Fr - m* ) plane is concluded. It is found that the critical velocity of each cavity type is reduced with increasing density ratio of the impact sphere, and the rebound phenomenon only forms in the case of low-density m* <1. The numerical results are in good agreement with the experimental measurements, and reveal details of cavity flow structures for different types, indicating that impact of sphere with higher density ratio generates faster air flow into the splash crown, greater impact pressure and closure pressure. According to the analysis of the measured trajectory, velocity, and acceleration, it is found that the lighter sphere is easier affected by forces, especially at pinch-off. The difference between the total hydrodynamic force coefficients and drag coefficients is found significantly related to the volume of the cavity attached to the immersion sphere.